Growth analysis of sunflower in a Cerrado Oxisol with different levels of basis saturation - Amabile, Renato Fernando; Guimarães, Daniel Pereira; Neto, Austeclínio Lopes de Farias (Pesquisa Agropecuaria Brasileira, 2003)
In order to study the growth cycle of five sunflower cultivars, four experiments were carried out under four levels of basis saturation (18%, 35%, 56% and 77%), obtained with the application of dolomitic limestone in an acidic Red Latosol, clay texture (Tipic Haplusthox). Weekly growth data were fitted using the Logistic, three parameters Weibull and four parameters Generalized Logistic (a special case of Richards function) functions. Among the models used, the Logistic function obtained was the best growth data fitting. The NLIN procedure of SAS statistical package was used for fitting the data through the interactive process of DUD method. Cultivars were grouped according to final size and growth rates by a cluster analysis using the complete linkage method and by the Euclidian distance. Sunflowers growth reduced in all cultivars at 18% basis saturation level. At 35% basis saturation level, the best results were achieved for cultivar M734. In other instances, the best growth results were obtained between 56% and 77%. For cultivars EMBRAPA 122 and M738, growth rates were reduced when basis saturation was increased to 77%. The cultivar EMBRAPA 122 presented initial higher growth rate and lower plant height at the end of vegetative cycle.